Autism spectrum traits predict higher social psychological skill - Gollwitzer, Anton (Proc Natl Acad Sci U S A, 2019)
Social-cognitive skills can take different forms, from accurately predicting individuals’ intentions, emotions, and thoughts (person perception or folk psychology) to accurately predicting social phenomena more generally. Past research has linked autism spectrum (AS) traits to person perception deficits in the general population. We tested whether AS traits also predict poor accuracy in terms of predicting generalized social phenomena, assessed via participants’ accuracy at predicting social psychological phenomena (e.g., social loafing, social projection, group think). We found the opposite. In a sample of ∼6,500 participants in 104 countries, AS traits predicted slightly higher social psychological skill. A second study with 400 participants suggested that heightened systemizing underlies this relationship. Our results indicate that AS traits relate positively to a form of social cognitive skill—predicting social psychological phenomena—and highlight the importance of distinguishing between divergent types of social cognition.